Other 7TM proteins in GtoPdb v.2023.1 - Bonner, Tom I. (IUPHAR/BPS Guide to Pharmacology CITE, 2023)
These proteins are predicted to have 7TM domains, but functional studies have yet to confirm them as G protein-coupled receptors.